Moderate to vigorous-intensity continuous training versus highintensity interval training for improving VO2max in women: A systematic review and meta-analysis - Lindner, R.; Raj, I. S.; Yang, A. W. H.; Zaman, S.; Larsen, B.; Denham, J. (International Journal of Sports Medicine, 2023)
Traditional continuous training and high-intensity interval training (HIIT) can increase maximal oxygen uptake (VO2max). However, there is conflicting evidence regarding which form of training demonstrates the greatest improvements to VO2max, and data in women is sparse. We conducted a systematic review and meta-analyses to assess whether moderate to vigorous-intensity continuous training (MVICT) or HIIT was superior at improving VO2max in women. Randomised controlled and parallel studies examined the influence of MVICT and/or HIIT on VO2max in women. There was no statistical difference in VO2max improvements after training between women in the MVICT and HIIT cohorts (mean difference [MD]: -0.42, 95%CI: -1.43 to 0.60, p>0.05). Both MVICT and HIIT increased VO2max from baseline (MD: 3.20, 95% CI: 2.73 to 3.67 and MD: 3.16, 95% CI 2.09 to 4.24, respectively, p<0.001). Greater improvements in VO2max were observed in women who participated in more training sessions in both training formats. Long-HIIT was superior to short-HIIT protocols at increasing VO2max. Although MVICT and long-HIIT sessions elicited greater increases in VO2max in younger women compared to short-HIIT protocols, these differences were negligible in older women. Our findings suggest MVICT and HIIT are equally effective strategies for improving VO2max and indicate an effect of age on its response to training in women.